Video Blogging in the Digital Era for Learning English Speaking - Izatussariroh Izatussariroh (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
AbstractIn language communication there are various skills that need to be mastered, ranging from reading, writing to speaking. In this study, the author will examine the use of vlogs as a medium of learning to speak in English at IAIN Surakarta more specifically at the sharia faculty and the faculty of usuludin dakwah. The study uses descriptive qualitative methods. The findings were obtained that the vlog media was able to increase student motivation and improve students' abilities or skills, especially in speaking English. Moreover, it can increase self-confidence in students in speaking or daily activitiesKeywords: Vlog, speaking, English